Unveiling the rhizosphere microbiome of Dendrobium: mechanisms, microbial interactions, and implications for sustainable agriculture - Sarsaiya, Surendra; Jain, Archana; Singh, Ranjan; Gong, Qihai; Wu, Qin; Chen, Jishuang; Shi, Jingshan (Frontiers in Microbiology, 2025)
The rhizosphere microbiome plays a critical role in plant health and productivity by fostering beneficial microbial interactions that support nutrient cycling, stress tolerance, and disease suppression. In the context of Dendrobium, understanding its interactions is essential for optimizing cultivation and promoting sustainable agricultural practices. This review explores the rhizosphere microbiome of Dendrobium, focusing on the mechanisms and microbial interactions that contribute to plant health, stress tolerance, and growth and their implications for sustainable agriculture. This study highlights the diverse composition of microbial communities in the Dendrobium rhizosphere, including key bacteria (e.g., Pseudomonas fluorescens and Bacillus subtilis), fungi (e.g., Glomus spp.), and biocontrol agents (Trichoderma spp.), and discusses their roles in nutrient cycling, disease suppression, and plant growth promotion. This review emphasizes the significance of plant-microbe signaling, such as the production of flavonoids, phytohormones, and strigolactones, in shaping the microbial environment and enhancing plant resilience. Additionally, it addresses modern techniques for analyzing microbial communities, including metagenomics and next-generation sequencing, and their applications in advancing precision agriculture. Future research should focus on bridging knowledge gaps related to genotype-microbiome interactions, exploring emerging microbial consortia and enhancing the integration of microbiome management in precision agriculture systems to improve plant health and productivity.